Online Training in Mind-Body Therapies: Different Doses, Long-term Outcomes - Kathi J. Kemper MD, MPH; Nisha Rao BA; Gregg Gascon PhD; John D. Mahan MD (Journal of Evidence-Based Complementary & Alternative Medicine, 2017)
Background. There is a high rate of burnout among health professionals, driving diverse attempts to promote resilience and well-being to counter this trend. The purpose of this project was to assess the dose-response relationship between the number of hours of online mind-body skills training for health professionals and relevant outcomes a year later. Methods. Among 1438 registrants for online training (including up to 12 hours of training on mind-body practices) between December 2013 and November 2015, we analyzed responses from the first 10% who responded to an anonymous online survey between December 1, 2015 and February 1, 2016. Questions included the type and frequency of mind-body practice in the past 30 days and whether the online training had any impact on personal life or professional practice. Standardized measures were used to assess stress, mindfulness, confidence in providing compassionate care, and burnout. Results. The 149 respondents represented a variety of ages and health professions; 55% completed one or more mind-body training modules an average of 14 months previously. Most (78%) engaged in one or more mind-body practices in the 30 days before the survey; 79% reported changes in self-care and 71% reported changes in the care of others as a result of participating. Increasing number of hours of training were significantly associated with practicing mind-body skills more frequently; increasing practice frequency was associated with less stress and burnout, which were associated with missing less work. Greater practice frequency was also associated with improvements in stress, mindfulness, and resilience, which were associated with increased confidence in providing compassionate care. Conclusion. Online training in mind-body therapies is associated with changes in self-reported behavior one year later; increasing doses of training are associated with more frequent practice which is associated with less stress, burnout, and missing work, and higher levels of mindfulness, resilience, and confidence in providing compassionate care. Additional studies are needed to compare mind-body skills training with other interventions designed to improve resilience and compassion while decreasing burnout in health professionals.